2023
DOI: 10.3389/fphar.2023.1097206
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of artemisinin and its derivatives in managing kidney diseases

Abstract: Artemisinin, an antimalarial traditional Chinese herb, is isolated from Artemisia annua. L, and has shown fewer side effects. Several pieces of evidence have demonstrated that artemisinin and its derivatives exhibited therapeutic effects on diseases like malaria, cancer, immune disorders, and inflammatory diseases. Additionally, the antimalarial drugs demonstrated antioxidant and anti-inflammatory activities, regulating the immune system and autophagy and modulating glycolipid metabolism properties, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“…Some studies have found that artemisinin has some toxicity, 38 so is DHA, a derivative of artemisinin, to be toxic as well? DHA has been reported to treat kidney disease, 39 but at the same time this author suggests that it is not clear whether it has other toxicities if used in long‐term, low‐dose therapy. These need to be explored in more studies to confirm the safety of DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that artemisinin has some toxicity, 38 so is DHA, a derivative of artemisinin, to be toxic as well? DHA has been reported to treat kidney disease, 39 but at the same time this author suggests that it is not clear whether it has other toxicities if used in long‐term, low‐dose therapy. These need to be explored in more studies to confirm the safety of DHA.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that AG has the potential to treat DCM by reducing inflammation and oxidative stress, and its mechanism may be related to NF-κB and NOXs/Nrf2 signaling pathways. Artemisinin and allicin (AA) have anticancer, antioxidant, and anti-inflammatory biological activities ( Zhou et al, 2022 ; Jin et al, 2023 ) and have been proved to be used in clinical anti-myocardial fibrosis ( Kong et al, 2023a ). Kong et al (2023a) found that the cardiac function of STZ-induced diabetic rats was damaged, and AA could improve these damages.…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%
“…Numerous studies have reported that Smad2/3 positively regulates cell fibrosis-like change and inflammation in renal interstitial fibrosis 6 , 7 . In addition, expression of Smad2/3 in the nucleus can aggregates in the renal tubular cell and accelerate CKD progression 8 , 9 . Therefore, the key to anti-fibrosis is to regulate the expression of Smad2/3 protein.…”
Section: Introductionmentioning
confidence: 99%